2007
DOI: 10.1002/pon.1208
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐dimensional quality of life among long‐term (5+ years) adult cancer survivors

Abstract: Survival from cancer has improved over the past decade resulting in more long-term survivors. The literature on multi-dimensional quality of life (QOL) among long-term (5+ years) adult survivors is reviewed for each of seven cancer sites (i.e. breast, ovarian, cervical, prostate, colorectal, head and neck, and Hodgkin's disease survivors). Overall, long-term survivors experience good to excellent QOL. Physical domain QOL was the most frequently measured while spiritual domain QOL was the least frequently measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
3
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(162 citation statements)
references
References 64 publications
(329 reference statements)
8
138
3
13
Order By: Relevance
“…One such study from the United States reported that older young adults expressed a need for improved age-appropriate information and support (such as fertility options and psychological counseling) and that younger respondents wanted treatment options that least interfered with their lifestyle 13 . General health and wellbeing, sexuality, and a lack of social support have been cited as important issues for young adults, but are often poorly understood during cfc in this population 14 . Other studies provide evidence supporting the benefits of social support, counselling, and therapeutic intervention for the emotional, functional, and symptom-related adjustments associated with cancer survival 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…One such study from the United States reported that older young adults expressed a need for improved age-appropriate information and support (such as fertility options and psychological counseling) and that younger respondents wanted treatment options that least interfered with their lifestyle 13 . General health and wellbeing, sexuality, and a lack of social support have been cited as important issues for young adults, but are often poorly understood during cfc in this population 14 . Other studies provide evidence supporting the benefits of social support, counselling, and therapeutic intervention for the emotional, functional, and symptom-related adjustments associated with cancer survival 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…The most important task is to provide a social support system and rehabilitation for patients with long-term physical, mental and functional problems after cancer treatment, with the goal of improving long-term HRQOL, on which social support has a great effect [5,8,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Health-related quality of life (HRQOL) is a multidimensional, multifaceted concept that includes the influence of disease and treatment on the patient's life, with QOL being an important outcome of cancer therapy [3,4]. The improvement of overall HRQOL after surgery for breast cancer is generally dependent on the time from diagnosis to treatment [5]. However, breast cancer patients after diagnosis have poorer physical functioning in comparison with healthy controls [6][7][8][9], and more frequent malaise [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Za důležité považujeme především to, že nemocný jedinec vnímá svou kvalitu života a mění svůj názor na svět i sebe samotného. Otázkou kvality života osob s onkologickým onemocněním se zabývala řada autorů (Bloom, Petersen & Kang, 2007;Hacker, 2008;Cadmus, Salovey, Yu, Chung, Kasl & Irwin, 2009). Kvalita života je veličinou vícerozměrnou, dynamickou, bez jednotného teoretického základu.…”
Section: úVodunclassified